Analysis of Financial Report Audit Planning Based on Public Accontant Professional Standards (Case Study on Kap Dony and Ramli) - Tampong, Gabriel; Yogismara, I.B.Putra; Wahyuni, Ni Nyoman Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Audit planning in a public accounting firm is a important is an part of producing quality audit reports the higher the quality of a public accounting firm, the higher the demand for the public accounting firm for the services offered. the more important the preparation and planning that is done so that the report produced is as expected. This Study aims to determine the Financial Statement Audit Planning model carried out by the Public Accounting Firm Dony & Ramli is in accordance or not in accordance with the Auditing Standards set by the Indonesian Association of Public Accountants in the SPAP. In this Study the data collection method used Interview and Documentation techniques. The results of this Study indicate that the Financial Report Audit Planning at Dony & Ramli Public Accounting Firm is in accordance with the Public Accountant Profession Standards issued by the Indonesian Assocation of Public Accountants.